Anthropometric features of Altai Youth Sambo Wrestlers; Journal of Physical Education and Sport (JPES); Vol. 16, iss. 2 - Makhalin A. V. Adu Vasiljevich; Savchenko E. L. Elena Leonidovna; Tokmasheva M. A. Marina Anatoljevna; Tokmashev D. M. Denis Mikhailovich (2016, 2016)
Title screen